Directorial Work of Taboo in Contemporary Iraqi Theater Performances (The Play Ya Rab as a Model) (Al-Academy, 2026)
" Taboo" is a term whose historical roots go back to the origins of humanity since the earliest times. Historical anthropological studies have revealed the relationship between humans and "taboo," as two points of convergence between concepts that evolved with the evolution of human society. Taboos can change depending on natural, social, political, psychological, and even physical variables. Psychology shares this concept with political science, sociology, and anthropology. These sciences export their dominant concepts and influences on humans, given that humans live in the environment they are influenced by and are influenced by. These taboos later become value constants, inherited beliefs, or religious legislation through sacred texts that impose their sanctity on humans. The first chapter dealt with the research problem, which was represented by the following question (What are the directorial concerns of the Iraqi director in his treatment of the concept of taboo in his theatrical performances?), the importance of the research, the aim of the research, the limits of the research, and the definition of the terms included. As for the second chapter, the researcher divided it into two sections: The first section: The intellectual and functional references of the concept of taboo: The second section: The directorial concerns of taboo in international theatrical experiences: In the third chapter, the researcher dealt with the research community, the research methodology, and the analysis of the play (Oh God). The fourth chapter dealt with the most important results and conclusions, then recommendations and suggestions, then a review of sources and references